The gut microbiota-inflammation-HFpEF axis: deciphering the role of gut microbiota dysregulation in the pathogenesis and management of HFpEF - Zhou, Shenghua; Zhou, Xuan; Zhang, Panpan; Zhang, Wei; Huang, Jinli; Jia, Xuzhao; He, Xiaole; Sun, Xin; Su, Hui (Frontiers in Cellular and Infection Microbiology, 2025)
Heart failure with preserved left ventricular ejection fraction (HFpEF) is a disease that affects multiple organs throughout the body, accounting for over 50% of heart failure cases. HFpEF has a significant impact on individuals’ life expectancy and quality of life, but the exact pathogenesis remains unclear. Emerging evidence implicates low-grade systemic inflammation as a crucial role in the onset and progression of HFpEF. Gut microbiota dysregulation and associated metabolites alteration, including short-chain fatty acids, trimethylamine N-oxides, amino acids, and bile acids can exacerbate chronic systemic inflammatory responses and potentially contribute to HFpEF. In light of these findings, we propose the hypothesis of a “gut microbiota-inflammation-HFpEF axis”, positing that the interplay within this axis could be a crucial factor in the development and progression of HFpEF. This review focuses on the role of gut microbiota dysregulation-induced inflammation in HFpEF’s etiology. It explores the potential mechanisms linking dysregulation of the gut microbiota to cardiac dysfunction and evaluates the therapeutic potential of restoring gut microbiota balance in mitigating HFpEF severity. The objective is to offer novel insights and strategies for the management of HFpEF.